Compliance and accountability: Evidence from a field experiment in Argentina - Krzysztof Krakowski; Lucas Ronconi (Inter-American Development Bank (IDB), 2023)
Does compliance with low-cost civic duties increase demand for social accountability? We address this question by conducting a field experiment at train stations in Buenos Aires. We create exogenous variation in compliance with paying the public transportation fare by i) highlighting sanctions for non-compliance and ii) appealing to compliance norms whereby 90 percent of passengers pay the fare. We find that both sanctions and norms treatments raise compliance. However, only appeals to compliance norms make treated passengers more willing to sign a petition demanding quality public transportation service-our measure of demand for social accountability. To probe the mechanisms explaining these patterns, we show that compliance invoked by adherence to norms makes subjects feel more entitled to demand accountability and trust the government to respect this right to a greater extent. Our findings suggest that raising compliance through appeals to social norms may thus have wider benefits for civic behaviors.
Keywords: D91; H26; O12; 330; Compliance; Accountability; Norms; Sanctions; Argentina